Using Storytelling to Heal Trauma and Bridge the Cultural Divide Between Veterans and Civilians. Issue 8 (17th November 2017) - Mamon, Daria; McDonald, Elise C.; Lambert, Jennifer F.; Cameron, Amy Y.
ABSTRACT: There is a growing disconnect between the Veteran and civilian communities related to their understanding of war-related trauma, postdeployment reintegration difficulty, and the experience of Memorial Day. A therapeutic way to bridge this divide is through community storytelling. This paper describes a program development project at a Veterans Affairs Medical Center that was created to increase the connection between these communities. Using storytelling, six Veterans shared their personal experiences with a civilian audience in honor of Memorial Day. Qualitative data on the impact of the program is reported, and suggestions for future application and research are discussed.